Effect of environmental and nutritional management during the transport of O. niloticus fry: Welfare indicators and productive performance - Bermúdez-Lara, Jonathan; Pascual-Jiménez, Cristina; Álvarez-González, Carlos; Albertos-Alpuche, Pedro J.; Martínez-Yáñez, Rosario (Revista Colombiana de Ciencias Pecuarias, 2025)
Background. The transport of juvenile tilapia (Oreochromis niloticus) is a critical phase in aquaculture production, where environmental and nutritional management may significantly influence animal welfare and productive performance. Objectives. This study aimed to evaluate the combined effect of water-to-oxygen ratios in transport bags and the type of diet provided before and after handling on welfare indicators and growth parameters of tilapia fry. Methods. A two experiment (3 × 2 factorial) were conducted, testing three oxygen supplementation levels (10, 15, and 20 L) in transport bags (equivalent to water-to-oxygen ratios of 1:1, 1:1.5, and 1:2), two diets (control and functional) before transport, and two diets (control and functional) after transport. Blood samples were collected at 0, 4, and 28 hours post-transport to evaluate glucose, lactate, and hematocrit as welfare indicators, while final weight, specific growth rate, and feed efficiency were measured after a 28-day period. Results. The 1:2 water-to-oxygen ratio was the most effective, maintaining dissolved oxygen above 3 mg L⁻¹ and promoting superior productive performance. All fish exhibited physiological stress responses after 4 hours of transport, as reflected by elevated glucose, lactate, and hematocrit values. However, partial recovery was observed after 28 hours, especially in fish previously fed the functional diet, which showed lower increases in hematological parameters. The best productive performance was recorded in fish feed a functional diet prior to transport and a control diet afterward, suggesting a beneficial pre-conditioning effect of the functional additives, coupled with an improved post-transport protein supply. Conclusions. An integrated management strategy that includes adequate oxygen supplementation (1:2 water-to-oxygen ratio) and the strategic use of functional additives before transport followed by a balanced control diet afterward, enhances both welfare and growth outcomes in tilapia fry. These findings provide valuable insights for optimizing handling practices and supporting sustainable and efficient aquaculture systems.